Kesalahan Umum dalam Pola Asuh Anak dan Dampaknya Terhadap Perkembangan - Aurel Salbila Putri; Ismaniar Ismaniar; Lili Dasa Putri (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to comprehensively examine various forms of common mistakes that parents often make in parenting, identify the factors causing these mistakes, analyze their negative impacts on children's physical, emotional, social, and moral development, and formulate strategies and practical solutions for improving parenting more effectively and positively. Problems with wrong parenting, such as inconsistency, over-indulgence, and lack of emotional validation, often occur without parents realizing it, potentially causing long-term psychological and social problems in children. The method used in this writing is a literature review (descriptive-analytical) based on the results of writing in the working area of Ulee Kareng Health Center and data from BPS (2024), as well as a review of theories of child development and parenting. The results of the study show that inappropriate parenting errors have significant impacts, such as decreased self-confidence in children, anxiety, difficulty socializing, and lack of independence, all of which emphasize the importance of responsive and consistent parenting. Therefore, parenting education and the implementation of positive parenting strategies that emphasize open communication, empathy, and consistency are essential to support optimal child growth and development.